2022
DOI: 10.1002/qj.4381
|View full text |Cite
|
Sign up to set email alerts
|

A convection‐permitting numerical study of diurnal cycles of pre‐summer rainfall over southern China

Abstract: In this study, the convection‐permitting model (CPM) with 3‐km horizontal resolution has been used to investigate the simulated ability on diurnal cycles of pre‐summer rainfall over southern China with various subregions and rainfall systems. Compared with the observations, the model captures the peak time of nocturnal rainfall in the western inland related to the eastward‐propagating rainfall system over the eastern slope of the Yungui Plateau. The simulated eastward‐propagating rainfall system moves a short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…The spatial distributions of total annual mean precipitation amount (PA) of all the rainfall events and the PA of intense RREs based on the station data and CMPA have been shown, respectively, in Figure 7. Both the station data and CMPA illustrate the obvious rainfall centres are over coastal region and northeastern inland region of Guangdong related to the complex topography (Chen et al ., 2015a; Shou et al ., 2020; Lu et al ., 2022). The differences between station observations and CMPA are very small indicating that CMPA is also reliable for the following study.…”
Section: The Definition and Characteristics Of Presummer Intense Rres...mentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial distributions of total annual mean precipitation amount (PA) of all the rainfall events and the PA of intense RREs based on the station data and CMPA have been shown, respectively, in Figure 7. Both the station data and CMPA illustrate the obvious rainfall centres are over coastal region and northeastern inland region of Guangdong related to the complex topography (Chen et al ., 2015a; Shou et al ., 2020; Lu et al ., 2022). The differences between station observations and CMPA are very small indicating that CMPA is also reliable for the following study.…”
Section: The Definition and Characteristics Of Presummer Intense Rres...mentioning
confidence: 99%
“…Due to the special geographical location of PRD, the heavy rainfall events are also influenced by the land–sea circulation, mountain–plain solenoid (MPS) circulation, synoptic system and large‐scale circulation including tropical cyclones, SCS summer monsoon, subtropical ridge of high pressure in western North Pacific (Chen et al ., 2014; 2016; Li & Zhou, 2015; Jiang et al ., 2017; Huang et al ., 2018). Previous studies have proved there are two precipitation peaks over PRD that one is late afternoon rainfall peak with local convection due to the solar heating and another is morning rainfall peak owing to enhanced nocturnal low‐level southwesterly flows bringing moisture transport (Yu et al ., 2014; Du & Chen, 2019; Li et al ., 2020; Lu et al ., 2022). Hence, the heavy rainfall events in PRD have multiscale features that can be classified as local rainfall events (LREs) related to convective clouds and regional rainfall events (RREs) associated with organized mesoscale or frontal systems (Toews et al ., 2009; Moron et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The morning rainfall inland differs from the eastward-propagating rainfall system on the eastern slope of the Yungui plateau. The intensified southwesterly winds during late night or early morning, along with their interaction with the topography or front, may amplify the development of nocturnal rainfall before the arrival of eastward-propagating rainfall systems [25]. However, the relationship between the inland rainfall system in GD and the eastward-propagating rainfall systems from Guangxi (GX) is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…CPMs have demonstrated their added values in various aspects of climate simulation, such as precipitation intensity (Lind et al 2020), diurnal cycle (Guo et al 2020), and land-sea breeze (Cafaro et al 2019). Studies have documented CPM-simulated diurnal variations and extreme precipitation over China (Lu et al 2022;Guo et al 2020;Dong et al 2022), revealing that CPMs excel in representing extreme precipitation and diurnal cycle in both Tibetan Plateau and eastern China (Ma et al 2021;Qing & Wang, 2021;Li et al 2021). However, it has been observed that the simulation capabilities of CPM may be sensitive to regional locations to some extent, resulting in distinct projected extreme precipitation changes over different areas (Kouadio et al 2020).…”
Section: Introductionmentioning
confidence: 99%